CHARACTER EDUCATION FROM THE PERSPECTIVE OF ISLAMIC BASIC EDUCATION IN PRIMARY SCHOOL (MI/SD) - Delimanugari, Daluti; Sibawaihi, Sibawaihi (Jurnal As Sibyan, 2024)
This research discusses how to implement character education from an Islamic basic education perspective. The approach in this research uses literature study, namely collecting data from various appropriate literature sources, such as; books, articles, theses and other documents. The discussion in the article, namely character education in Islam, aims to build human beings with noble character through the values taught by Allah and the Messenger of Allah which can be applied in basic education. These values include traits such as siddiq, amanah, tabligh, and fathanah, which are the basis for human interaction with God, fellow humans, and the environment. Character education must start from an early age and include various methods such as example, stories, habits and dialogue. Character education in Islam also includes harmonious relationships with Allah, fellow humans, and the environment, all of which are regulated in the Koran and hadith. The implementation of character education is very important in forming individuals who have good morals and are beneficial to the wider community